Chelyabinsk, Zond IV, and a possible first‐century fireball of historical importance. (12th March 2015) - Hartmann, William K.
Abstract: The well‐recorded Chelyabinsk event, the Tunguska event, and the re‐entry of the Zond IV vehicle offer opportunities to compare reactions of modern eyewitnesses to eyewitness accounts of possible ancient fireball events. The first‐century book, Acts of the Apostles, gives three separate descriptions of a bright light "from heaven, " which occurred probably in the 30s (C.E.) near Damascus, Syria. The details offer a strikingly good match to a Chelyabinsk‐class or Tunguska‐class fireball. Among the most impressive, unexpected consistencies with modern knowledge is the first‐century description of symptoms of temporary blindness caused by exposure to intense radiation, matching a condition now known as photokeratitis. An analysis of the re‐entry of debris from the Russian Zond IV over the eastern United States in 1968 shows how actual perceived phenomena in an unfamiliar natural celestial apparition are often conceived by the observer in terms of current cultural conceptions, and it is suggested that this happened also in the first‐century case.